Gotong royong melawan korupsi demi mengembalikan jati diri bangsa indonesia yang berintegritas dan bermartabat - Mubarok, Akmal Rijal (Maliki Interdisciplinary Journal, 2026)
Corruption is often seen as a complex legal issue, when in fact its root cause is closely related to the fading of noble values in our daily lives as citizens. This article discusses how the spirit of mutual cooperation (gotong royong), which is the authentic identity of the Indonesian nation, can be used as a primary weapon to fight the culture of corruption from the simplest levels. So far, the fight against corruption has seemed to be solely the task of state institutions, even though the power of social monitoring through collective action is much more effective in creating a clean environment. Using a light sociological approach, this article explores ways to reawaken a sense of shame and collective responsibility to reject all forms of gratification and dishonesty. The discussion results show that when gotong royong is revived as a fortress of integrity, we are not only fighting corruption but also restoring the dignity of the Indonesian nation in the eyes of the world. The conclusion of this paper invites every citizen, especially the younger generation, to make honesty a collective movement for a better future for Indonesia.